Factores limitantes para la incorporación de atractivos complementarios del paquete turístico del centro histórico de Trujillo para su comercialización. - Gavidia Vela, Luciana Anais (2019)
The present thesis entitled Limiting factors for the incorporation of complementary attractions of the touristic package of the Historical Center of Trujillo for its commercialization, has as objective to identify the factors that limit the incorporation of complementary attractions in the tourist package Trujillo, commercialized by the operating agencies of the Center Historical. _x000D_ The investigation determined that one of these factors is the lack of interest and ignorance of travel agents in the planning and preparation of tourist packages, where only 20% of this staff knows and complies with the technical processes for this purpose, which are first to identify the attractions, second to formulate the tourist circuit, third to select the suppliers, fourth to formulate the tourist program and fifth to elaborate the cost. _x000D_ It is the scarce budget to manage the complementary attractions and include them in the tourism products offered to tourists visiting the city, another factor that was found to be limiting the investment of the owners of the agencies in new alternatives that include existing complementary attractions in the city. _x000D_ Finally, it was found that in Trujillo we have complementary attractions that would enrich the offer that we already have in the local market, these would be the horses of passage, the marinera, the agrotourism, the handicraft workshops of the Moche countryside, the caballitos de totora, the tour of the leather, the gastronomy of the province of Trujillo, the traditional candy stores, the municipal theater, the spring corso and the shopping tour. _x000D_ _x000D_ For this research the scientific methods were used: Deductive - Inductive which has allowed to identify the reality of the Trujillo destination offer and to determine the limiting factors for the incorporation of complementary attractions, the Descriptive with which certain characteristics of the touristic packages were described of Trujillo offered by the local travel agencies, and the Analytical - Synthetic that was applied to decompose said limiting factors; each of them with their respective techniques and instruments, which have allowed the field stage to be carried out correctly.